AI Threat or Partner Narratives in Lecturer Student Discourse: A CDA of Polarization and Legitimacy - Rama Dwika Herdiawan; Yayah Nurhidayah; Trian Pamungkas; Yaniar Ratna Dewi (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2026)
This study examines how lecturers and students discursively construct generative artificial intelligence (GenAI) as either a threat or a partner in higher education, and how these competing stances are legitimized in everyday academic communication. Guided by Critical Discourse Analysis, the study analyzes 124 GenAI-relevant statements (74 spoken; 50 written) drawn from assignment briefings, classroom discussions, consultation meetings, LMS announcements, rubric explanations, emails, and class-group chats in a bounded university context. Polarization was coded as Threat, Partner, or Hybrid/Ambivalent, while legitimation strategies were traced using Theo van Leeuwen's framework (authorization, moral evaluation, rationalization, and mythopoesis), complemented by discursive legitimation perspectives. Findings show that Threat-oriented statements (n=52) slightly outnumber Partner-oriented statements (n=35), with Hybrid